A Qualitative Comparative Analysis of cross-sectoral bioresource residue flows from agriculture, forestry, and aquaculture: the crucial role of non-biobased sectors in the development of the circular bioeconomy - Otte, Pia Piroschka; Adamsone-Fiskovica, Anda; Žabko, Oksana; Kerge, Kristiina; Šūmane, Sandra; Shvaichenko, Svetlana; Veveris, Armands; Mincyte, Diana (Frontiers in Sustainability, 2025)
IntroductionPrimary production sectors of the bioeconomy—agriculture, forestry, and aquaculture (AFA)—have a significant role in the transition towards the circular economy (CE). Their generated residues can be transformed into renewable biomass resources that serve as an input in the production processes within AFA and other sectors. Valorization of residues in new value-added products and development of new value chains often require cross-sectoral collaboration. In this paper, we use the conceptual framework of industrial symbiosis and identify patterns and test selected influencing factors of cross-sectoral flows of bioresource residues generated in AFA.MethodsWe apply a Qualitative Comparative Analysis (QCA) to perform a comparative analysis of 107 circular initiatives in the biobased sectors in five countries—Estonia, Latvia, Lithuania, Norway, and Ukraine. We focus on the (i) sectors involved in the flow of bioresource residues, (ii) companies’ motivation to initiate circular flows, and (iii) type of bioresource residues used.ResultsThe analysis of these factors reveals three pathways leading to cross-sectoral flow of bioresource residues: a combination of agriculture with a non-AFA sector (such as energy, food, and feed industries); a combination of aquaculture with the absence of forestry; and a combination of forestry with the absence of aquaculture. Motivational factors such as revenues and legal requirements were not confirmed as decisive for cross-sectoral resource flows.DiscussionThe results show that non-AFA sectors appear central in the development of industrial symbiosis for the circular bioeconomy, and collaboration between AFA and non-AFA sectors needs to be expanded for a better valorization of bioresource residues.